2010
DOI: 10.5152/jtgga.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Experience of our surgery in iatrogenic vesicovaginal fistulas

Abstract: Objective: In this study, transvesical and transvaginal approaches used in our clinic for the treatment of gynecologic iatrogenic vesicovaginal fistulas are discussed. Material and Methods: 11 patients with vesicovaginal fistula admit-ted to the Department of Urogynecology, Zeynep Kamil TeachingResearch Hospital between 2005-2009 were enrolled in our study. Transvesical and transvaginal fistula repair were performed on all patients. All patients were treated by surgical repair, 4 cases by a classic transabdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The mean age of the patients in the present study was 37.05 ±8.08 years. In recent studies by Wadie and Kamal ( 15 ) in 2011 and Karateke et al in 2010 ( 16 ), the median age at presentation was >35 years, which is similar to the present study. Wall et al ( 17 ) in 2004 reported a higher incidence of VVF in a younger population; the mean age was 27 years (range, 13-20 years).…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the patients in the present study was 37.05 ±8.08 years. In recent studies by Wadie and Kamal ( 15 ) in 2011 and Karateke et al in 2010 ( 16 ), the median age at presentation was >35 years, which is similar to the present study. Wall et al ( 17 ) in 2004 reported a higher incidence of VVF in a younger population; the mean age was 27 years (range, 13-20 years).…”
Section: Discussionsupporting
confidence: 92%
“…The age of the subjects in this study ranged from 13-55 years with a mean of 28±11.1 years. This is similar to the findings of Kumar et al, Karateke et al and Amitava et al [12][13][14] This age range is within the child-bearing age of women as well as the age when obstetric and gynaecologic surgeries are most commonly performed. The youngest patient in this study was 13 years at the time of presentation.…”
Section: Discussionsupporting
confidence: 91%
“…5 However, the Þ stula patients pose a considerable challenge for the surgeon in terms of success due to multiple factors responsible for the success(type of Þ stula, previous repair attempt, parity, size of Þ stula, accessibility). 6,7 Among those, history of previous repair attempts has been reported to be the most consistently related to the success of Þ stula repair. 8,9 As prior knowledge of the predictors of success helps to counsel the patient and to individualize the management, we did a retrospective analysis on prospectively collected data of patients who attended our center for urogenital Þ stula management.…”
Section: Introductionmentioning
confidence: 99%